3 Rs Approaches For The Study Of Sig- Naling Events Triggered By Pesticide Induced Neurotoxicity - Conde, Melisa Ailén (2023)
Maneb (MB), a dithiocarbamate pesticide, can cross the blood-brain barrier and is considered an environmental risk factor associated with Parkinsonism. Our aim was to characterize redox signaling during MB-induced neurotoxicity in different experimental models according to the 3Rs principle. Taking into account full Replacement we firstly exposed neuronal cell line cultures to MB and we detected increased expression levels of the redox sensitive transcription factor Nrf2 and its regulator Sirt1. Neuronal MB exposure also triggered the increase of lipid peroxidation, GSH depletion, GpX4 downregulation and mitochondrial alterations, indicating that ferroptosis is involved in the mechanism of cell death. We confirmed these results in a model of relative Replacement by using glial mixed primary cultures. We also demonstrate that Nrf2/Sirt1 signaling is a protective strategy against neurotoxicity. Based on these results and with the aim of evaluating phenotypical aspects for establishing a preclinical model, we design an experimental paradigm with C57BL/6 mice. Following Refinement criteria, treatments were performed with the supervision of a veterinarian who care the animal welfare during the entire procedure. C57BL/6 mice (18-20g) were intraperitoneally injected with MB (100 mg/kg) for 6 weeks. Behavioral tests (Open Field and Rotarod) were performed on week 3 and 6 of treatment. One day after the last administration, animals were sacrificed by cervical dislocation. Forebrain, midbrain and hindbrain were separated for molecular determinations. To apply the Reduction criteria all other animal organs were used for related investigations. MB-treated animals showed a decrease in total distance travelled, supported and unsupported rears and in falling latency. These results indicate that MB neurotoxicity triggers a parkinsonian phenotype in C57BL/6. The results presented here constitute a platform for toxicological and preclinical studies according to 3Rs principles.